A non-intrusive approach of goal-oriented error estimation for evolution problems solved by the finite element method - Chamoin, Ludovic; Ladevèze, Pierre (European Journal of Computational Mechanics, 2008)
In this article, we set up a non-intrusive procedure that yields for strict and highquality error bounds of quantities of interest in linear viscoelasticity problems solved by means of the Finite Element Method. The non-intrusive feature is achieved by introducing, via a partition of unity, enrichment functions in the solution of the adjoint problem (handbook techniques). The resulting goal-oriented error estimation method is thus easy to implement in a FE code and enables to consider trully pointwise quantities of interest.